ORIENTED PROGRAMS OF TEACHING A FOREIGN LANGUAGE FOR NON-LINGUISTIC AREAS OF BASIC EDUCATION - Shakirova, Saida (Журнал иностранных языков и лингвистики, 2023)
Our article deals with oriented foreign language teaching programs for non-linguistic areas of basic education.